Strategic Business Models for Manufacturing SME Transformation: A Qualitative Research - Joanna HELMAN Maria ROSIENKIEWICZ Mariusz CHOLEWA; Mateusz MOLASY (Communications of International Proceedings, 2025)
Small and medium-sized manufacturing enterprises (SMEs) are under increasing pressure to align with Europe’s industrial transformation priorities, particularly digitalization, sustainability, and innovation. While numerous business models exist to support this shift, SMEs often lack a clear framework to evaluate which models are both feasible and impactful within their specific operational context. This study addresses that gap by examining 14 transformation-oriented business models, each linked to practical business goals and derived from the Interreg Central Europe SMERF (SME Ready for the Future) project, spanning three strategic domains, namely Digital Manufacturing, Open Innovation and Sharing Economy, and Green and Circular Economy and Sustainability. Employing a qualitative, framework-driven methodology, the models were assessed through a Readiness and Complexity Matrix, which considers both their strategic impact and the barriers to implementation, including technological, financial, and organizational challenges. The analysis demonstrates that while the majority of models are highly relevant to the sector's transformation needs, complexity rather than readiness serves as the primary constraint, particularly for models that require digital infrastructure or ecosystem-level collaboration. The findings suggest that SMEs would benefit from a phased approach to innovation adoption, beginning with low-complexity models and advancing toward more integrated solutions as internal capabilities mature. Furthermore, the study underscores the need for policy and support mechanisms that differentiate interventions according to model complexity, thereby enabling more SMEs to transition toward resilient, future-oriented business practices.
Keywords: SME transformation; business goals; manufacturing SMEs; readiness and complexity matrix